Odpowiedzi

2010-02-04T16:19:38+01:00
B) 3=1a+b
9=3a+b ___________
6=2a
a=3
3=1*3+b
b=0
y=3x


c)2=1a+b
4=3a+b
__________
2=2a
a=1
2=1*1+b
b=1
y=x+1


d)5=4a+b
9=6a+b
__________
2=2a
a=1
5=4*2+b
b=-3
y=2x-3


e)-1=2a+b
-2=3a+b
___________
a=-1
1=2*(-1)
1=-2+b
b=-3
y=-x-3


f) 0=-2a+b
2=-6a+b
_________
2=-4a
a= -1/2
0=-2*(-1/2)+b
b=-1
y= -1/2x-1



ta "______" to ma być pod tym równaniem - to jest metoda tych samych współczynników. ;-)
2010-02-04T16:27:01+01:00
f(x) = ax + b
powstana układy równań
b) f(1)=3 i f(3)= 9
3 = a*1+b/ *(-1)
9 = 3a +b
-3 = -a - b
9 = 3a +b
6 = 2a
3=a
3 = 3+b
0=b
f(x) = 3a
c) f(1)= 2 i f(3)= 4
2 = a +b /(-1)
4 = a*3 +b
-2 = -a -b
4 = 3a +b
2= 2a
1=a
b = 2-1 = 1
f(x) = x +1
d) f(4) = 5 i f(6) = 9
5 = 4a+b/*(-1)
9 = 6a +b
-5 = -4a-b
9 = 6a +b
4 = 2a
2=a
5 = 2*4 +b
5-8 =b
-3 = b
f(x) = 2x -3
e) f(2) = -1 i f(3) = -2
-1 = 2a+b /*(-1)
-2=3a+b
1 = -2a -b
-2=3a+b
-1 = a
-2 = 3 * (-1) +b
-2+3 = b
1=b
f(x) = -x +1

f) f(-2)= 0 i f(-6)= 2
0 = -2a +b /*(-1)
2 =-6a +b
0 = 2a -b
2 =-6a +b
2 = -4a
-1/2 = a
0 = -2 * (-1/2) +b
0 = 1+b
-1 = b
f(x) = -1/2x -1